IMPLEMENTATION OF MODULAR MANUFACTURING IN THE CLOTHING INDUSTRY IN KWAZULU-NATAL: A CASE STUDY - K. Ramdass; L. Pretorius (South African Journal of Industrial Engineering, 2012)
ENGLISH ABSTRACT: There are many challenges facing the clothing and textile industry in countries worldwide, and South Africa is no exception. Intense competition from both the domestic and international markets is crippling both the clothing and textile industries. However, with a reservoir of experience and expertise within the industry, it could re-establish itself as a forceful industry with an ability to challenge competitors both domestically and internationally through a focus on added value, exceptional quality, and the effective application of all resources through technological innovation. One such innovation in the clothing industry in South Africa may be the use of modular manufacturing. Qualitative narrative interviews and text analysis results on the experiences of individuals through the implementation of modular manufacturing are presented and evaluated as a case study. AFRIKAANSE OPSOMMING: I'n Verskeidenheid uitdagings staar die kleding- en tekstielindustrie wêreldwyd in die gesig. Suid-Afrika is ook hieraan blootgestel. Intense kompetisie in nasionale en internasionale markte het tans ’n besonder negatiewe uitwerking op die kleding- en tekstielindustrie. Daar is egter ’n goeie bron van ervaring en kennis in die bedryf wat kan meehelp om die besondere kompetisie die hoof te bied. Dit kan geskied deur te fokus op toegevoegde waarde, uitsonderlike kwaliteit, en die effektiewe aanwending van hulpbronne deur tegnologiese innovasie. Een so ’n innovasie in die Suid-Afrikaanse kledingindustrie kan die aanwending van modulêre vervaardiging wees. Kwalitatiewe narratiewe resultate van onderhoude, sowel as teks- en inhoudanalise van die ervarings van werknemers tydens die implementering van modulêre vervaardiging, word as ’n gevallestudie aangebied.